PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL DISCOVERY LEARNING PADA MATERI SEGIEMPAT DAN SEGITIGA UNTUK SISWA KELAS VII SMP/MTs - Sri Atika Annovli; Elfis Suanto; Sakur Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by limited mathematics learning tools using learning approaches and models that can support learning in the curiculum 2013. The purpose of this research is to produce mathematical learning tools consist of syllabus, lesson plan and student worksheet that use learning discovery model in quadrilateral and triangular topic for valid students of junior high School and qualify the practicality requirement. The research method used is the ADDIE development model, which consists of Analyze, Design, Development, Implementation, Evaluation. The research instrument used is validity instrument and practicality instrument. The validity instrument is a validation sheet to assess the feasibility of syllabus, lesson plans and student worksheet. The practicality instrument is in the form of observation sheet of learning process implementation and questionnaire of student response . Learning device developed are validated by three validators. The research trials were conducted in SMPN 17 Pekanbaru which is tested in a small group and large group. Small group trial aims to assess the practicability based on student response questionnaire, while the large group to assess the practicability based on the observation sheet of learning process implementation and student response questionnaire. Based on the data analysis, it can be conclude that the average value for syllabus are 4,6; lesson plans are 4,4; student worksheet are 4,4 from the 5,00 scale, so the resulting device is catagorized as very valid.. The student worksheet valued as very practical with mean score for small group and large group testing are 92,1% and 93,4%. The lesson plan also valued as very practical with mean percentage is 98,33%. These categories mean that the lesson plan and student worksheet are feasible to used in school.Key Words: Development Research, Mathematics Learning Tools, Discovery Learning Model, ADDIE Model